UN SAN FRANCESCO DI CARAVAGGIO - Salvemini, Francesca (Archeomatica, 2012)
Una semiologia dei dipinti di S. Francesco nel Novecento più spesso attribuiti a Caravaggio, in rapporto al "S. Francesco in atto di ricevere le stimmate” della Chiesa di S. Anna dei Lombardi a Napoli, annotato al pittore alla sua morte nella biografi a di Giulio Mancini. Dai dati storiografici il Santo emerge per il carattere stupefacente di realismo della fi gura con i piedi, negli approcci critici di analisi stilistico-iconografica, archivistica e diagnostica del secolo scorso nelle tipologie: inginocchiato di profilo e di fronte, seduto e disteso. La massa sferica del cranio ruota solo nei S. Gerolamo Borghese e di La Valletta e, nella proiezione basale completa, nella Resurrezione di Lazzaro. The analysis processes focuse a semiological result of one canvas over the heterogeneous St. Francis' shapes referred to Caravage The analysis processes focuse a semiological result of one canvas over the heterogeneous St. Francis' shapes referred to Caravage, primarily introduced on the early 20th century between 1593-1700 time-lapse, on obtained by several sources and paintings, when the context of copysts and their appreciation in the past had began to appear as originals. Scale images, both masses and canvas, of halfl engths are claimed as giants in the Christ crowned with thorns in Wien, and collapse as in the Captures of Christ in Dublin and Odessa, maintaining the painter any circular motion to any distance including the Christ figure in the small space between the presence of observer by each enlarged Passion canvas of Supper at Emmaus. The underdrawing results by neutralized scale-off scanner diagnostics Multi-Nir (2010) on paintings of Caravaggio as Supper at Emmaus of Brera and by X-Rays as Emmas of London show different frames and supports. An iconological approach to the ‘Nude young servant', the Fuga dell'Ortolano Giustiniani, also related in the1791 to the artist by Mariano Vasi, and including in the narrative scenes of Malchus only Marcus' Gospel in the painting published by B. Nicolson recently affi rmable as the Sustermans' Taking of Christ (2003, 2009), is the print in The Vaticano of E. Pistolesi to G. Muziano (Orvieto).